PEMASARAN MADU MAKIN MANIS DENGAN KEAHLIAN MEDIA SOSIAL - Mei Ie; Salsabilla Ayundha Martsha Buana (Jurnal Bakti Masyarakat Indonesia, 2025)
W Trigona Honey MSME in North Lombok is a business engaged in the cultivation of high quality trigona honey. However, there are certainly major challenges faced, namely limitations in the utilisation of digital marketing and effective business management. Currently, sales are still limited to the local market due to a lack of skills in utilising social media and digital-based marketing strategies. In fact, the development of digital technology and the increasing number of social media users in Indonesia offer great opportunities for MSMEs to expand their market reach. The Community Service Programme (PKM) conducted by the Untar PKM Team aims to help Trigona Honey W MSMEs in improving digital marketing competencies, social media management, and understanding of sustainable entrepreneurship. This activity includes workshops that discuss online marketing strategies, the use of social media platforms such as Instagram, Facebook, and Tiktok, as well as the creation of interesting content. In addition, the training also covered market analysis, business planning, financial management, and branding strategies to improve product competitiveness. The results of this activity show that participants gained new insights as well as skills that can be implemented in their businesses. With more optimal utilisation of social media and the implementation of effective marketing strategies, W Trigona Honey MSMEs are expected to increase brand awareness, reach a wider market, and strengthen their competitiveness in the honey industry.   ABSTRAK UMKM Madu Trigona W di Lombok Utara merupakan usaha yang bergerak dalam budidaya madu trigona dengan kualitas tinggi. Namun, pastinya terdapat tantangan utama yang dihadapi yaitu keterbatasan dalam pemanfaatan pemasaran digital dan manajemen bisnis yang efektif. Saat ini, penjualan masih terbatas pada pasar lokal karena kurangnya keterampilan dalam memanfaatkan media sosial dan strategi pemasaran berbasis digital. Padahal, perkembangan teknologi digital dan meningkatnya pengguna media sosial di Indonesia menawarkan peluang besar bagi UMKM untuk memperluas jangkauan pasar. Program Pengabdian kepada Masyarakat (PKM) yang dilakukan Tim PKM Untar ini bertujuan untuk membantu UMKM Madu Trigona W dalam meningkatkan kompetensi digital marketing, pengelolaan media sosial, serta pemahaman tentang kewirausahaan yang berkelanjutan. Kegiatan ini meliputi workshop yang membahas strategi pemasaran online, penggunaan platform media sosial seperti Instagram, Facebook, dan Tiktok, serta pembuatan konten yang menarik. Selain itu, pelatihan juga mencakup analisis pasar, perencanaan bisnis, pengelolaan keuangan, dan strategi branding untuk meningkatkan daya saing produk. Hasil dari kegiatan ini menunjukkan bahwa peserta mendapatkan wawasan baru serta keterampilan yang dapat diimplementasikan dalam bisnis mereka. Dengan pemanfaatan media sosial yang lebih optimal dan penerapan strategi pemasaran yang efektif, UMKM Madu Trigona W diharapkan dapat meningkatkan brand awareness, menjangkau pasar yang lebih luas, dan memperkuat daya saingnya di industri madu.